Social Safety Net Programs in Bangladesh: An Impact Study on Education, Health and Decision-Making Process of Women Beneficiaries - Islam, Md Nurul; Haque, Tawohidul; Mia, Md Tuhin (South Asian Journal of Social Sciences and Humanities, 2025)
Background: Social Safety Net Programs (SSNPs) in Bangladesh, such as the Old Age  Allowance (OAA) and Allowances for the Widowed, Deserted, and Destitute Women  (AWDDW), aim to alleviate poverty and empower vulnerable populations, particularly  women, by providing financial assistance to improve access to education, healthcare, and  decision-making. Objectives: This study evaluates the impact of SSNPs on three key areas:  (1) children’s education, (2) women’s health, and (3) their participation in household  decision-making, aiming to identify areas for program improvement. Methods: A quantitative  study was conducted with 180 women beneficiaries across Dhaka and Kurigram districts.  Data was collected through structured questionnaires and analyzed using descriptive and  inferential statistics in SPSS. Results: The study revealed that 65.6% of women beneficiaries  had children currently studying, with 66.1% affirming that the allowance supported their  education. A statistically significant relationship was found between children’s education  status and the perceived helpfulness of the allowance (P
Keywords: Social Safety Net; Old Age Allowance; Allowance for Widow; Education; Health; Decision Making Process; Women; Bangladesh